Modernização gerencial e desempenho da justiça eleitoral: a implantação do planejamento estratégico no Tribunal Regional Eleitoral da Bahia - BERTONCINI, Isabella (2014)
This case study is an analysis of the implementation of strategic management at the Regional Electoral Court of Bahia (TRE-BA), in the period 2010-2012, and its effects. To do so, we sought to present its management structure, analyze the motivation for the adoption of strategic management, study TRE-BA‟s strategic plan and its management model, discuss the transformations undertaken in that Court from the implementation of the strategic management model, and evaluate the potential gains in performance with the strategic management model. Thus, documentary research was conducted, combined with interviews with managers and questionnaires with the servers of the court. This demonstrated that the implementation of strategic planning brought, in general, performance gains, particularly as to expedite the trial of older processes, and in regards to agility in the handing of elections and the access to justice for society.